Pedestrian behaviour at unsignalized zebra crossing : A case study in UMP Gambang campus - Azlina, Ismail; Liyana, Mohamed Yusof; Intan Suhana, Mohd Razlan (Institute of Physics, 2023)
The interest toward promoting walking culture has been increased dramatically especially in many cities across the nation. This is also included universities worldwide that have started seeking ways to increase pedestrian activities. Hence, campus planners must address the mobility and accessibility needs of pedestrian in their communities to ensure safety, functionality and conducive living and learning environment. This study was conducted to evaluate the pedestrian perception and behaviour towards the unsignalized zebra crossing in campus environment. To achieve the objective of this study, the unsignalized zebra crossing in UMP Gambang campus was selected as study location. This study was conducted using a quantitative study by means of questionnaires distribution and pedestrian movement data collection. Then Average Index Method was performed to indicate the pedestrian perception towards the crossing facility performances. The result shows that the zebra crossing was efficient and safe from the respondent's perspective. Other than that, gender and platoon significantly influenced the crossing speeds. The outcomes from this study were hoped to bring some understanding to the university on the pedestrian's behaviour for future planning and pedestrian safety.